A Review of Histiocytic Diseases of Dogs and Cats. (January 2014) - Moore, P. F.
Histiocytic proliferative disorders are commonly observed in dogs and less often cats. Histiocytic disorders occur in most of the dendritic cell (DC) lineages. Canine cutaneous histiocytoma originates from Langerhans cells (LCs) indicated by expression of CD1a, CD11c/CD18, and E-cadherin. When histiocytomas occur as multiple lesions in skin with optional metastasis to lymph nodes and internal organs, the disease resembles cutaneous Langerhans cell histiocytosis of humans. Langerhans cell disorders do not occur in feline skin. Feline pulmonary LCH has been recognized as a cause of respiratory failure due to diffuse pulmonary infiltration by histiocytes, which express CD18 and E-cadherin and contain Birbeck's granules. In dogs and cats, histiocytic sarcomas (HS) arise from interstitial DCs that occur in most tissues of the body. Histiocytic sarcomas begin as localized lesions, which rapidly disseminate to many organs. Primary sites include spleen, lung, skin, brain (meninges), lymph node, bone marrow, and synovial tissues of limbs. An indolent form of localized HS, progressive histiocytosis, originates in the skin of cats. Hemophagocytic HS originates in splenic red pulp and bone marrow macrophages in dogs and cats. In dogs, histiocytes in hemophagocytic HS express CD11d/CD18, which is a leuko-integrin highly expressed by macrophages in splenic red pulp and bone marrow. Canine reactive histiocytic diseases, systemic histiocytosis (SH) and cutaneous histiocytosis, are complex inflammatory diseases with underlying immune dysregulation. The lesions are dominated by activated interstitial DCs and lymphocytes, which invade vessel walls and extend as vasocentric infiltrates in skin, lymph nodes, and internal organs (SH).